Electrophoretic karyotype of environmental isolates of Paracoccidioides brasiliensis (1999)
ABSTRACT: Five of the 12 environmental isolates of the dimorphic fungus Paracoccidioides brasiliensis known to date, were analysed by contour-clamped homogeneous electric field gel electrophoresis (CHEF). The electrophoretic pattern was shown to consist of five bands, with molecular size ranging from 3·2 to 10 Mb, a model quite similar to the one found in the clinical isolates previously tested and used here as controls. However, one of the bands in the environmental isolates had a lesser weight (7·2 Mb), than the one corresponding to the clinical counterparts (8·8 Mb). This resulted in a smaller genome, approximately 29·7 Mb. The small differences that were found indicate the presence of chromosome polymorphism in this fungus.